Integrating electrodermal biofeedback into pharmacologic treatment of grand mal seizures - Scrimali, Tullio; Tomasello, Damiana; Sciuto, Massimo (Frontiers in Human Neuroscience, 2015)
Electrodermal activity (EDA) and electrodermal biofeedback, when integrated with pharmacologic treatments, indicate promising methods for the treatment of grand mal seizures. They can be used to monitor patient arousal and help patients learn new strategies to better cope with stress and anxiety. Our proposed method can possibly reduce the number of crises for patients who are dependent on pharmacologic therapy and can improve their quality of life. This article describes the scientific background of electrodermal monitoring and electrodermal biofeedback for patients affected by grand mal seizures. In this study, we have reported a clinical case study. The patient was treated for 2 years with electrodermal biofeedback to augment pharmacologic treatments. The trial has been designed in accordance with “n = 1 case study research”. Our results have shown that our methods could achieve a significant reduction in grand mal seizures and sympathetic arousal when applied. The patient under consideration was also relaxed and exhibited greater competency to cope with stress. Additionally, the patient’s sense of mastery and self-efficacy was enhanced.